ANALISIS PESAN MORAL KARAKTER BUYA HAMKA PADA FILM BUYA HAMKA VOLUME 1 - Nofia Natasari; Endi Kurniawan (Komsospol, 2022)
"Buya Hamka Volume 1" is a biographical film that explores the life of Buya Hamka, an influential scholar and writer from Indonesia. This abstract presents an in-depth analysis of the moral message reflected in Buya Hamka's life journey in the film. The aim of the research is to understand the aspects of morality in the character Buya Hamka in the film Buya Hamka volume 1. Including spirituality, role modeling, social involvement and moral conflicts faced by the main character in the film. This research uses a qualitative method with a narrative paradigm approach. In the aspect of spirituality, the film shows Buya Hamka's spiritual journey, depicting his search for the meaning of life and religious values. Buya Hamka's example and ethics are reflected in every action and attitude, highlighting that his life decisions are consistent with the moral values he adheres to. Buya Hamka's social involvement in education, social welfare and political struggle is interpreted as a moral message about social responsibility and concern for society. Moral conflict becomes a dramatic moment in his life journey, where Buya Hamka is tested by the ethical values he believes in. His life decisions reflect his moral integrity and shape his character. Overall, this film not only provides a biographical picture of Buya Hamka, but also presents an in-depth reflection on moral and ethical values that can inspire viewers in living their daily lives.